EVALUATION OF THE IMPLEMENTATION OF OCCUPATIONAL HEALTH AND SAFETY MANAGEMENT SYSTEM (SMK3) AT PT. PELABUHAN - Dzaky Ekki Wibowo; Sajiyo Sajiyo (Jurnal Ekonomi, 2023)
Issues related to occupational safety and health in general are still neglected, especially in Indonesia. This can be proven by the high rate of work accidents. At PT. Pelabuhan recorded several work accident incidents of 469 cases in the 2019-2022 period. The occupational safety and health management system (OSHMS) is a form of prevention and reduction of the risk of work accidents. This study aims to evaluate the application of OSHMS PT. Pelabuhan as an effort to develop the application of OSHMS and improve HSSE performance at PT. Pelabuhan. This study will take OSHMS data according to PP 50 of 2012 with 166 criteria (Advanced Level). Based on the results of the audit and analysis carried out, it is known that the number of criteria fulfilled is 156 criteria with a percentage of 93.97% and there are 10 criteria of non-conformity percentage 6.03% (minor category). These results state the level of implementation of OSHMS at PT. Pelabuhan is included in the (Satisfactory) category. Furthermore, corrective actions and recommendations will be made for non-conformity in OSHMS.